Impacts of Sandstorms on Chemistries of Ambient PAHs in a Small City in North China - Li, Zhiyong; Zhai, Zhen; Liu, Jixiang; Chen, Lan; Ren, Zhuangzhuang; Liu, Chen; Zhan, Ziyi; Yue, Ziyuan; Zhu, Wenjia; Wei, Jihong; Gao, Huiying; Guo, Songtao (Aerosol and air quality research, 2023)
Sandstorm events frequently perplex northern China, addressing the people’s concern due to subsequent increases in the toxicity and carcinogenicity of PM 2.5 -bound PAHs (PB-PAHs) in receptor area of sand dust. Here, we enacted a field campaign in a small city between Beijing and Baoding in spring of 2021 covering the sandstorm period (SSP) and non-sandstorm period (NSSP) to examine the sandstorm impacts on chemistries of PB-PAHs. SSP exhibited a slightly high average PAH concentrations of 10.3 ng m −3 than 9.16 ng m −3 in the NSSP. At the same time, the average PM 2.5 concentrations obviously increased from 60.7 µg m −3 to 75.2 µg m −3 . Positive matrix factorization (PMF) analysis manifested that sandstorm largely enhanced the oil leakage and combustion (OLC) fractions from 18.0% in the NSSP to 34.4% in the SSP. Potential source contribution function (PSCF) indicated that OLC partly came from sandstorm origin area–Inner Mongolia. Low diagnostic ratios of FA/(FA + PY) in the SSP also indicated OLC was more important. Accordingly, the largest contributor of incremental lifetime cancer risks (ILCRs) changed from vehicle exhaust (VE) (36.2%) in the NSSP to OLC (34.4%) in the SSP. VE and industrial emission (IE) contributions decreased obviously due to emission control and traffic limitation in the SSP. Coal burning (CB) still held a high contribution to PAHs regardless of the implementation of “coal to gas” law in the sampling area. In addition, sandstorms increased the levels of high molecular weight PAHs (HMW-PAHs) with high toxicity by 4.07%. ILCRs for adults and children increased from 3.90 × 10 −7 to 4.74 × 10 −7 and from 2.41 × 10 −7 to 2.93 × 10 −7 , respectively, in the SSP, which should be more concerned.